(untitled) (UBS Scientific Bulletin, 2025)
In the article, it is no secret that global climate change, which will cause new epidemics and global population of bacteria, is the most urgent issue today, because the atmosphere is filled with various harmful gases and dust. It caused a number of other problems as a result of its sudden change and its serious impact on human health, the population suffers from various diseases caused by harmful epidemics and bacteria, and the quality of agricultural crops deteriorates. It is intended to understand the effects of climate change, assess its dangerous consequences, prevent it, introduce and implement measures to adapt to the conditions of climate change in Uzbekistan to the population and students, and the health of the population is in their own hands. it is intended to explain to them that it is.